Analisis Pengukuran Kinerja Dengan Pendekatan Sustainability Balanced Scorecard - putri, atina rokhmani; Zuhroh, Diana; Sihwahjoeni, Sihwahjoeni (Akuisisi : Jurnal Akuntansi, 2024)
Sustainability balanced scorecard (SBSC) modified from balanced scorecard (BSC) integrates environmental indicators into four balanced scorecard perspectives to obtain balanced, comprehensive, and strategic environmental performance information. This study aims to measure environmental and social performance using four SBSC perspectives, namely learning and growth, internal business processes, customers, and finance. The research is a study of dental clinics using quantitative descriptive analysis. The results of the study found that in general since the Covid-19 pandemic, NDC Esthetic Dental Clinic has made various efforts so that this business can survive and continue to grow even though this is a major challenge for health sector businesses due to government regulations, limited communication and interaction with people in this case patients. During the 2019-2020 period, the performance of NDC Esthetic Dental Clinic was analyzed based on the Sustainability Balanced Scorecard and was considered good.